2008
DOI: 10.1097/pas.0b013e3181484f1e
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Intraductal Papillary-mucinous Carcinoma of the Pancreas: Clinicopathologic Study of 104 Intraductal Papillary-mucinous Neoplasms

Abstract: Invasive intraductal papillary-mucinous carcinoma (I-IPMC) is a heterogeneous entity with various postoperative outcomes. The aim of this study is to characterize early-stage I-IPMC with nonaggressive characteristics. One hundred and four patients with intraductal papillary-mucinous neoplasm (IPMN) were clinicopathologically investigated. The lesions were classified into 53 noninvasive IPMNs (adenoma, borderline, and noninvasive IPMC) and 51 I-IPMCs on the basis of the WHO classification. I-IPMCs were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 22 publications
3
57
1
2
Order By: Relevance
“…Colloid carcinoma is generally identified in association with intestinal-type IPMN and tubular carcinoma is generally found in association with pancreatobiliary IPMN [9] . Immunohistochemical studies have identified differences in the expression of the glycoproteins, MUC1, MUC2 and CDX2, between invasive colloid and tubular carcinoma IPMN, further suggesting that these entities are distinct from a molecular standpoint [10][11][12] . Colloid carcinoma associated with IPMN generally expresses both MUC2 and CDX2, markers of intestinal differentiation, a characteristic of more indolent carcinomas [13] .…”
Section: Subtypementioning
confidence: 99%
“…Colloid carcinoma is generally identified in association with intestinal-type IPMN and tubular carcinoma is generally found in association with pancreatobiliary IPMN [9] . Immunohistochemical studies have identified differences in the expression of the glycoproteins, MUC1, MUC2 and CDX2, between invasive colloid and tubular carcinoma IPMN, further suggesting that these entities are distinct from a molecular standpoint [10][11][12] . Colloid carcinoma associated with IPMN generally expresses both MUC2 and CDX2, markers of intestinal differentiation, a characteristic of more indolent carcinomas [13] .…”
Section: Subtypementioning
confidence: 99%
“…A half of surgically resected IPMNs are intraductal papillary-mucinous adenoma (IPMA) or borderline IPMN even under current international criteria (21), and it is still unclear when they change to noninvasive intraductal papillary-mucinous carcinoma (IPMC), how long IPMC retains a status of "carcinoma in situ", and when IPMC achieves invasiveness. Particularly, invasive carcinoma originating from intraductal papillary-mucinous carcinoma (IC-IPMC) showed similar malignant behavior compared with conventional invasive ductal carcinoma both clinically and histologically (15). Minimally invasive IPMC (MI-IPMC) has been categorized within the classification of pancreatic carcinoma used by pancreatic IPMNs at Tokai University Hospital, Japan.…”
mentioning
confidence: 99%
“…Among them, 2 patients without mural nodules had invasive carcinomas; however, both of them were minimally invasive carcinomas defined by Nara et al [10] as within 5 mm invasion to the pancreatic parenchyma. They reported that minimally invasive IPMNs are associated with no LNM and a 100% disease-specific survival rate [10]. Thus, lymph node dissection might be able to be diminished during pancreatectomy for IPMNs without mural nodules.…”
Section: Discussionmentioning
confidence: 99%